Two new genera and species of flat bugs from the Philippines (Hemiptera: Heteroptera: Aradidae) - Heiss, Ernst (Zootaxa, 2018)
From the Philippines a new genus of Mezirinae: Cagayanacoris gen.nov. with the species C. menardi sp.nov. and a new genus of Carventinae: Vizcayaptera gen.nov. with the species V. minuta sp.nov. are described and illustrated.